2022
DOI: 10.1161/jaha.122.027305
|View full text |Cite
|
Sign up to set email alerts
|

Differing Impact of Preterm Birth on the Right and Left Atria in Adulthood

Abstract: Background Preterm birth affects 10% of live births and is associated with an altered left ventricular and right ventricular phenotype and increased cardiovascular disease risk in young adulthood. Because left atrial (LA) and right atrial (RA) volume and function are known independent predictors of cardiovascular outcomes, we investigated whether these were altered in preterm‐born young adults. Methods and Results Preterm‐born (n=200) and term‐born (n=2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…In a study by Arnott et al , 48 SGA adults had larger LV volumes and lower LVSV compared to individuals of average size for gestational age. Lewandowski et al reported a greater LV mass, smaller chamber volumes, and worse LV strain in individuals with a history of preterm birth compared with controls, 49 findings that were replicated in relation to the atria, 50 in a subsequent study in an adolescent 51 and a further adult cohort. 52 Importantly, these changes are not benign: they have been shown to relate to a reduced myocardial functional reserve and an increase in diffuse myocardial fibrosis.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In a study by Arnott et al , 48 SGA adults had larger LV volumes and lower LVSV compared to individuals of average size for gestational age. Lewandowski et al reported a greater LV mass, smaller chamber volumes, and worse LV strain in individuals with a history of preterm birth compared with controls, 49 findings that were replicated in relation to the atria, 50 in a subsequent study in an adolescent 51 and a further adult cohort. 52 Importantly, these changes are not benign: they have been shown to relate to a reduced myocardial functional reserve and an increase in diffuse myocardial fibrosis.…”
Section: Discussionmentioning
confidence: 91%
“…Prior observational evidence suggests that preterm-born adults, when exposed to physiologic stress, may exhibit a response of exaggerated contraction, possibly indicating compensation for reductions in volumetric reserve. 50 , 55 …”
Section: Discussionmentioning
confidence: 99%
“…Our findings imply that low birth weight is linked to late‐onset CVD through mechanisms other than CHIP. Previous work has implicated changes in cardiac structure and function, 57 , 58 , 59 , 60 increased oxidative stress levels, 61 renin–angiotensin–aldosterone system imbalance, 62 and augmented systemic inflammation 63 , 64 as possible factors underlying the independent associations of low birth weight with incident CVD in adulthood. In contrast with low birth weight, the associations between high birth weight and late‐onset CVD appear to be predominantly mediated by conventional risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review reportied that adverse cardiometabolic consequences may not be limited to estreme and very preterm individuals (<28 and between 28 to 32 weeks respectively), with moderate to late preterm birth (between 32-36 weeks of gestation) also associated with increased risks of hypertension and diabetes (16). More adverse cardiac structure and function in people born preterm compared with terms have been reported (17,18), although studies with more also tend to have more limited sample sizes.…”
Section: Introductionmentioning
confidence: 99%